Proceedings of the 2019 Ahmad Dahlan International Conference Series on Pharmacy and Health Science (ADICS-PHS 2019) 2019
DOI: 10.2991/adics-phs-19.2019.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nanoemulgel Formula of Gold Particle-Vitamin E and in Vivo Test

Abstract: Gold is a substance that can be used as a collagen forming catalyst, it can help regenerate the skin. Vit. E is a natural antioxidant compound that can be used to help regenerate and brighten the skin. Gold is a metal so it is difficult to apply into the skin. Gold and vit. E are formulated with SNEDDS (Self Nano Emulsifying Drugs Delivery System) technique, in order to reduce the size and dispersing of gold particles homogeneously. SNEDDS formula consists of olive oil, tween 80 (surfactant), propylene glycol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Accordingly, the particle sizes of emulgel and nanoemulgel demonstrated a good distribution and fell within a narrow range of sizes. Our findings are in agreement with Ermawati et al, who showed a particle size of 150 nm for the formulation of nanoemulgel gold [ 41 ]. Moreover, Dhawan et al, recorded the particle size of piroxicam nanoemulgel to be within the nano size range (125 nm) [ 42 ].…”
Section: Resultssupporting
confidence: 93%
“…Accordingly, the particle sizes of emulgel and nanoemulgel demonstrated a good distribution and fell within a narrow range of sizes. Our findings are in agreement with Ermawati et al, who showed a particle size of 150 nm for the formulation of nanoemulgel gold [ 41 ]. Moreover, Dhawan et al, recorded the particle size of piroxicam nanoemulgel to be within the nano size range (125 nm) [ 42 ].…”
Section: Resultssupporting
confidence: 93%
“…The thickness of the patch film affects the permeability of the drug to penetrate the film. The thicker film will reduce the permeability of the drug through the film and the coefficient of drug permeability through the film [7]. Patch thickness also affects the fragility of the patch.…”
Section: Physicochemical Properties Test Of Patch Moringa Oleifera Le...mentioning
confidence: 99%
“…The results of the analysis show that the variation ratio of PVA and alpha-cellulose polymers in Moringa oleifera leave ethanolic extract patch have no significant effect on the pH value between the patch formulas. High Moisture content caused patches to be easily overgrown with fungi and bacteria [7]. The moisture content test using a moisture analyzer.…”
Section: Physicochemical Properties Test Of Patch Moringa Oleifera Le...mentioning
confidence: 99%
See 1 more Smart Citation